A critical and exegetical commentary on Haggai, Zechariah, Malachi and Jonah - Mitchell, Hinckley Gilbert Thomas (International critical commentary on the Holy Scriptures of the Old and New Testaments, 1912)
Haggai and Zechariah / by H.G. Mitchell -- Malachi / by John Merlin Powis Smith -- Jonah / by Julius A. Bewer.